2016
DOI: 10.1371/journal.pone.0147771
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence Is Associated with Endothelial Dysfunction in Uremic Subjects on Hemodialysis

Abstract: BackgroundElevated levels of advanced glycation end products (AGEs) within tissues may contribute to endothelial dysfunction, an early indicator of atherosclerosis. We aimed to investigate whether levels of skin AGEs could be a useful marker to predict endothelial dysfunction in uremic subjects on hemodialysis.Methods and ResultsOne hundred and nineteen uremic patients on hemodialysis and 57 control subjects with moderate-to-high cardiovascular risk factors and without chronic kidney disease (CKD) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…In addition, the AGEs contributed to the progression of kidney disease in non-diabetic nephropathy, the possible mechanisms for this included binding to the RAGE, inducing oxidative stress, endothelial dysfunction, inflammation, and podocyte injury [ 32 ]. Another study reported significant increases of AGEs in HD patients with cardiovascular diseases, compared with the non-CKD group [ 33 ]. This implied that the increased accumulation of AGEs in the subjects with uremia might have been because of the increased oxidative stress, rather than the increased glucose burden alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AGEs contributed to the progression of kidney disease in non-diabetic nephropathy, the possible mechanisms for this included binding to the RAGE, inducing oxidative stress, endothelial dysfunction, inflammation, and podocyte injury [ 32 ]. Another study reported significant increases of AGEs in HD patients with cardiovascular diseases, compared with the non-CKD group [ 33 ]. This implied that the increased accumulation of AGEs in the subjects with uremia might have been because of the increased oxidative stress, rather than the increased glucose burden alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al proposed significantly higher skin AF in young adolescents of type 1 diabetes with retinopathy than those without retinopathy [ 18 ]. Higher skin AF associated with endothelial dysfunction [ 19 ] and arterial pulse wave velocity [ 20 ] has been described in subjects with end-stage renal failure. Recently, Sell et al proposed skin collagen fluorophore LW-1 to be a useful marker for the subclinical macrovascular disease in patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…When assessed using skin AF values, we observed a marked increase in vascular age, which is more than 10 years higher than the chronological age in patients with CKD. Vascular aging occurs along with endothelial dysfunction, vascular remodelling, inflammation, and increased stiffness, all of them previously associated with AGEs [ 16 , 38 ]. In this way, we observed a 3-fold increased risk of an atheromathous plaque in subjects with a skin AF value higher > 2.0 AU.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive loss of glomerular filtration rate (GFR) is associated with systemic inflammation, as well as with an imbalance between oxygen reactive species production and antioxidant defenses [ 14 , 15 ]. Increased circulating levels of AGEs are found in patients with CKD undergoing hemodialysis regardless, of the presence of T2D [ 4 , 16 ]. Some additional factors have been associated with AGEs accumulation in renal failure because of decreased glomerular filtration, intraperitoneal formation during the time course of peritoneal dialysis, or dietary intake [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%